Drug Transporters in the Kidney: Perspectives on Species Differences, Disease Status, and Molecular Docking - Zou, Wei; Shi, Birui; Zeng, Ting; Zhang, Yan; Huang, Baolin; Ouyang, Bo; Cai, Zheng; Liu, Menghua (Frontiers in Pharmacology, 2021)
The kidneys are a pair of important organs that excretes endogenous waste and exogenous biological agents from the body. Numerous transporters are involved in the excretion process. The levels of these transporters could affect the pharmacokinetics of many drugs, such as organic anion drugs, organic cationic drugs, and peptide drugs. Eleven drug transporters in the kidney (OAT1, OAT3, OATP4C1, OCT2, MDR1, BCRP, MATE1, MATE2-K, OAT4, MRP2, and MRP4) have become necessary research items in the development of innovative drugs. However, the levels of these transporters vary between different species, sex-genders, ages, and disease statuses, which may lead to different pharmacokinetics of drugs. Here, we review the differences of the important transports in the mentioned conditions, in order to help clinicians to improve clinical prescriptions for patients. To predict drug-drug interactions (DDIs) caused by renal drug transporters, the molecular docking method is used for rapid screening of substrates or inhibitors of the drug transporters. Here we review a large number of natural products that represent potential substrates and/or inhibitors of transporters by the molecular docking method.